Body weight, body composition and energy balance related behaviour during the transition to parenthood: study protocol of a multi-centre observational follow-up study (TRANSPARENTS) - Tom Deliens; Vickà Versele; Hannelore Vanden Eynde; Peter Clarys; Roland Devlieger; Annick Bogaerts; Leonardo Gucciardo; Annick Schreurs; Caroline Van Holsbeke; Dirk Aerenhouts (BMC, 2019)
Abstract Background The transition to parenthood is a cornerstone event for both parents, potentially leading to relevant changes in lifestyle and behaviour. In women, the metabolic changes during and after pregnancy and the deleterious effects of excessive gestational weight gain and postpartum weight retention have been extensively described. However, there is no full understanding about which specific energy balance related behaviours (EBRB) contribute to unfavourable weight gain and weight retention. Furthermore, information on how transition to parenthood affects men is lacking. Therefore, this study aims to investigate changes in body weight, body composition and EBRB in couples transitioning to parenthood. Methods TRANSPARENTS is a multi-centre observational follow-up study that focuses on body weight, body composition and EBRB during the transition to parenthood. Couples (women and men) will be recruited during the first trimester of their first pregnancy. Study visits will occur at four occasions (12 weeks of pregnancy, 6 weeks postpartum, 6 months postpartum and 12 months postpartum). Anthropometrics of the parents and new-borns will be assessed including body weight, height/length, body composition (using bio-electrical impedance analysis and measurement of four skinfold thicknesses (biceps, triceps, subscapular and supraspinal/suprailiac)) and waist and hip circumference. Dietary intake, physical activity, sedentary behaviour, smoking habits, sleeping pattern, fatigue, diet and exercise related partner support, mental health, breastfeeding, contraception use, and socio-demographics will be assessed using a questionnaire. In addition, accelerometry will be used to assess physical activity and sedentary behaviour objectively. Also data from women's medical record, such as pre-pregnancy weight and pregnancy outcomes, will be included. Multilevel modelling will be used to evaluate maternal and paternal changes in body weight, body composition and EBRB during and after pregnancy (primary outcomes). Multiple linear regression analyses will be performed to identify predictors of changes in body weight, body composition and EBRB. All analyses will be adjusted for possible confounders. Discussion TRANSPARENTS is a unique project identifying vulnerable parents and (un)favourable changes in EBRB throughout this potentially critical life period. Provided insights will facilitate the development of effective intervention strategies to help couples towards a healthy transition to parenthood. Trial registration Clinicaltrials.gov Identifier: NCT03454958. Registered March 2018.